Barefoot vs running shoes – Comparing 20m sprint performance, spatiotemporal variables and foot strike patterns in schoolchildren in the Western Cape - Murphy, Ian Desmond (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScSportSc)--Stellenbosch University, 2017